Covalent surface functionalization of nonwoven fabrics with controlled hydrophobicity, water absorption, and pH regulation properties. Issue 6 (27th August 2020) - Dan, Yoav; Buzhor, Marina; Raichman, Daniel; Menashe, Eti; Rachmani, Oren; Amir, Elizabeth
Abstract: A modular method for functionalization of nonwoven fabrics was developed using a two‐step process. In the first step, the fabrics were grafted with a linker molecule, 10‐undecenoyl chloride, via esterification, followed by attachment of a functional material under UV irradiation. Perfluorodecanethiol and 3‐mercaptopropionic acid (MPA) were connected to the linker‐modified fabrics using thiol‐ene click chemistry. Perfluorodecanethiol modified fabrics exhibited hydrophobicity with water contact angle of about 140° while MPA‐modified fabrics were able to lower the pH of a solution by about 1.6. We additionally demonstrated the possibility to connect functional polymers to the linker‐modified fabrics by radical graft polymerization of acrylic acid; this produced a thin layer of the polymer on the surface of the fabric. Fabrics modified with poly(acrylic acid) exhibited increased hydrophilicity with water contact angle of 0° for both cotton and viscose‐polyester fabrics, while the water absorption capability for polypropylene fabrics increased from about 50 to 1200%. Abstract :